2008
DOI: 10.1210/me.2008-0146
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of GPIHBP1, an Endothelial Cell Binding Site for Lipoprotein Lipase and Chylomicrons, Is Induced by Peroxisome Proliferator-Activated Receptor-γ

Abstract: Glycosylphosphatidylinositol-anchored high-density lipoprotein-binding protein 1 (GPIHBP1), a protein in the lymphocyte antigen 6 (Ly-6) family, plays a key role in the lipolytic processing of triglyceride-rich lipoproteins. GPIHBP1 binds lipoprotein lipase and chylomicrons and is expressed along the luminal surface of microvascular endothelial cells. Lipolysis is known to be regulated by metabolic factors and is controlled at multiple levels, including the number of LPL binding sites on capillaries. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 17 publications
3
61
2
Order By: Relevance
“…Angplt4 is a PPARregulated gene that is induced by PPAR␥ in adipocytes and PPAR␦ in macrophages (34,35). Although LpL is a source of ligands for PPAR activation (44,45), it is possible that adipose, like the liver, activates PPAR transcription factors using de novo synthesized fatty acids (46). In summary, upon deletion of LpL in adipocytes, we made several observations that provide novel insights into adipose tissue biology.…”
Section: Discussionmentioning
confidence: 99%
“…Angplt4 is a PPARregulated gene that is induced by PPAR␥ in adipocytes and PPAR␦ in macrophages (34,35). Although LpL is a source of ligands for PPAR activation (44,45), it is possible that adipose, like the liver, activates PPAR transcription factors using de novo synthesized fatty acids (46). In summary, upon deletion of LpL in adipocytes, we made several observations that provide novel insights into adipose tissue biology.…”
Section: Discussionmentioning
confidence: 99%
“…We expected to observe Gpihbp1 expression in endothelial cell lines, but this has not been the case. Davies et al (25) were unable to detect Gpihbp1 expression in rat heart microvascular endothelial cells, human umbilical vein endothelial cells (25), or bovine aortic endothelial cells (unpublished observations). Davies et al (25) also reported that primary endothelial cells from white adipose tissue lost nearly all Gpihbp1 expression after a single passage.…”
Section: Gpihbp1 Expression Is Regulatedmentioning
confidence: 94%
“…In embryoid bodies, GPIHBP1 is found in CD31-positive endothelial cells surrounding beating cardiomyocytes (25).…”
Section: Gpihbp1 Expression Is Regulatedmentioning
confidence: 99%
See 1 more Smart Citation
“…Because endothelial cells lose expression of GPIHBP1 when cultured (26), lentiviruses encoding S-protein-tagged mouse GPIHBP1 were transduced into endothelial cells and selected for stable transduction with puromycin as described previously (9). We have previously shown that GPIHBP1 expression levels in lentivirus-transduced RHMVECs are similar to those found in endothelial cells in vivo (9).…”
Section: Methodsmentioning
confidence: 99%